The Effect Of Percussive Therapy On Musculoskeletal Performance And Experiences Of Pain: A Systematic Literature Review - Lorna Sams; Ben L Langdown; Joan Simons; Jitka Vseteckova (International Journal of Sports Physical Therapy)
# Background